Comparative Studies of Value Management Practice on Facilities Management Structure Among Malaysia Higher Education Institution - Saidatul Nadirah; Ishak, Mohd Hafizal; Md Yassin, Azlina; Ahmad, Nurul Afiqah; Masram, Haidaliza; Thanaraju, Puvaneswary A/P (Research in Management of Technology and Business, 2026)
This study explores the implementation of value management (VM) in the facilities management (FM) structures of two Malaysian higher education institutions: Universiti Teknologi Malaysia (UTM) and Universiti Teknikal Malaysia Melaka (UTeM). The research evaluates the extent to which VM principles are integrated into FM practices and examines their impact on institutional operations. Findings reveal that UTeM demonstrates a higher level of VM adoption (14/19), highlighting its proactive approach to operational excellence, while UTM, with a score of 10/19, shows moderate implementation, hindered by a decentralized structure. Despite differences in organizational approaches, both universities aim to enhance resource utilization and financial sustainability. The study emphasizes the need for clear communication, alignment of strategies, and comprehensive value management frameworks to optimize facilities management in higher education institutions. The results offer insights into best practices and areas for improvement in the application of VM within FM practices.